The effectiveness of manual versus powered toothbrushes for plaque removal and gingival health: A meta-analysis - Akshay Vibhute; K L Vandana (Wolters Kluwer Medknow Publications, 2012)
Background: The aim of this systematic review and associated meta-analysis was to compare manual and powered brushes in relation to the removal of plaque and gingival health. Stain removal, adverse effects and microbiological evaluation cost were also considered. Materials and Methods: To be included in the review, a trial had to be a randomized-controlled trial (RCT) comparing manual and powered brushes. Trials confined to comparing different types of powered or different types of manual brushes were excluded. Split mouth designs were eligible. Trials with subjects of specific age group (18-25 years) were included. The primary outcomes were plaque and gingival health with data defined as short-term (0-28 days) duration were analyzed. Powered brushes were categorized into three groups depending on mode of action. Numerical data extracted were checked by a fourth reviewer for accuracy. Results: Three trials with full articles were identified. These include trials published between 2002 and 2005. The trials involved 56 subjects at baseline, without loss of subject for follow up. Powered brushes reduced plaque and gingivitis at least as effectively as manual brushing. Ionic brushes statistically significantly reduced plaque and gingivitis. Conclusion: In general there was no evidence of a statistically significant difference between powered and manual brushes. However, ionic brushes significantly reduce plaque and gingivitis in both the short-term evaluations. The clinical significance of this reduction is not known. Observation of methodological guidelines and greater standardization of design would benefit both future trials and meta-analyses.